A measure for feelings – using inclusive research to develop a tool for evaluating psychological therapy (Clinical Outcomes in Routine Evaluation – Learning Disability). (7th April 2013) - Brooks, Michelle; Davies, Stephanie; Twigg, Elspeth
Abstract : Accessible summary: In this article, we shall be talking about how a group of people with learning disabilities and therapists came together to make a questionnaire about feelings. We adapted a questionnaire called Clinical Outcomes in Routine Evaluation – Outcome Measure to make a version that was useful for people with a learning disability who go to therapy for help when they are feeling particularly unhappy. We wanted to help people with a learning disability and their therapists find out if the therapy was helping. This is called practice‐based evidence. The NHS now demands that all treatments can show that they work. We were all new to research, and we will describe how we developed ways of working together that meant everyone could contribute. This is called inclusive research. This was necessary because we all had different experiences that were valuable to the research and that we wanted to share. In particular, we wanted to find out how the experience of living with a learning disability affects feelings so that this could be included in the questionnaire. Inclusive working was important to make sure the questionnaire made sense and was easy to use for people with a learning disability. We will discuss how we made the questionnaire, called Clinical Outcomes in Routine Evaluation – Learning Disabilities, and how we carried out tests to find out if it was a good, reliable measure that showed how people's feelings changed over time when they received therapy. This is called psychometric testing. Finally, we summarise the results of the psychometric testing and discuss what will happen next. Summary: Psychological talking therapies are increasingly being sought by people when they are experiencing emotional difficulties. This is just as important for people with a learning disability as the general population but as with other services for this population, inclusion for therapy lags behind that of mainstream services. Similarly, tools for assessing the effectiveness of therapy for people with a learning disability are often limited and do not fully take account of the impact that living with a learning disability may have on peoples' feelings and sense of well‐being. It was for this reason that we, the authors of this article, a Dramatherapist and Specialist Counsellor got together with initially eight but subsequently five people with a learning disability to develop an outcome measure that would be accessible and have meaning for people with a learning disability. Clinical Outcomes in Routine Evaluation – Outcome Measure (Evans et al . J Ment Health, 2000;32, 144; Barkham et al . 1998) was selected as the measure to be modified and developed, as it was already a validated tool, was in widespread use across the country and was suitable for use across a whole range of therapeutic approaches. This article describes how inclusive research has been a key component in developing and psychometrically testing Clinical Outcomes in Routine Evaluation – Learning Disabilities. Using an outcome measure that is sensitive to the needs of people with a learning disability is a vital step towards providing evidence upon which best practice may be established.